Immune cell profiling of peripheral blood in long-term testicular germ cell tumor survivors - Kilikova, Kristina; Mlcakova, Andrea; Sestakova, Zuzana; Kalavska, Katarina; Adamikova, Kristyna; Obertova, Jana; Palacka, Patrik; Rejlekova, Katarina; Sycova-Mila, Zuzana; De Angelis, Valentina; Orszaghova, Zuzana; Lesko, Peter; et al. (Frontiers in Immunology, 2025)
IntroductionThis study addresses changes in peripheral blood immune cell composition and possible late effects of curative treatment in testicular germ cell tumors (GCT) survivors.MethodsWe analyzed the immunophenotype in peripheral blood obtained from 202 survivors treated at the National Cancer Institute in Bratislava by flow cytometry. The median long-term follow-up was 13 years (1-35). We divided the survivors into groups as follows: CT-chemotherapy (N = 141), RT-radiotherapy (N = 16), CTRT – chemotherapy + radiotherapy (N = 13), and the control group of patients under active surveillance - AS (N = 32).ResultsSurvivors treated with AS had a lower number of B-cells (mean ± standard deviation (SD) = 10.3 ± 3.5 vs 11.9 ± 4.2, p=0.04) compared to the CT group. Survivors treated with AS vs RT had a higher number of total lymphocytes (29.8 ± 7.7 vs 25.2 ± 6.3, p=0.04). In AS vs CTRT group B-cells (10.3 ± 3.5 vs 13.7 ± 5, p=0.01) and conventional dendritic cells (cDCs) (74.3 ± 11.8 vs 82.5 ± 6.7, p=0.04) showed lower numbers. Survivors treated with AS vs. ≤ 400 mg/m2 cumulative dose of cisplatin had fewer eosinophils (2.29 ± 1.5 vs 2.99 ± 1.7, p=0.03) and double-negative T-cells (DNT cells) (4.7 ± 3.4 vs 6.6 ± 6.6, p=0.04). In AS vs. ≥ 400 mg/m2, B cells counts were lower in the control group (10.96 ± 5.3 vs 12.3 ± 4.8, p=0.03); treatment with ≤ 400 mg/m2 vs. ≥ 400 mg/m2 resulted in higher counts of eosinophils (3.0 ± 1.7 vs 2.1 ± 1.7, p=0.00025) and DNT cells (6.7 ± 6.7 vs 4.9 ± 3.6, p=0.02).ConclusionsOur study demonstrates an association between both cisplatin-based chemotherapy and radiotherapy with specific immune cell populations, suggesting that these treatment modalities may exert long-term immunomodulatory effects.